FoMO and Gen Z Purchase Decisions: The Role of Brand Image, Influencer Marketing, and Online Customer Reviews on the TikTok Platform - Luh Gede Natasya Utari; I Gusti Ayu Agung Omika Dewi (Politeknik Siber Cerdika Internasional, 2026)
Background: This study is motivated by the growing phenomenon of social commerce on TikTok, which has transformed consumer purchasing behavior, particularly among Generation Z, through digitally driven trends. Objective: This study aims to analyze the influence of brand image, influencer marketing, and online customer reviews on the purchase decisions of Glad2Glow skincare products on TikTok, with Fear of Missing Out (FoMO) serving as a mediating variable among Generation Z consumers in Bali. Method: This research employs a quantitative approach using an explanatory research design. The population consists of Generation Z consumers in Bali who have purchased Glad2Glow products through TikTok Shop. The sampling technique applied is purposive sampling, yielding a sample of 180 respondents. Data were collected through online questionnaires using a Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares (SEM–PLS). Results: The findings reveal that brand image (β = 0.410, p < 0.001), influencer marketing (β = 0.270, p < 0.001), and online customer reviews (β = 0.278, p < 0.001) significantly influence purchase decisions (R² = 0.682). Brand image (β = 0.247, p < 0.001) and influencer marketing (β = 0.342, p < 0.001) significantly influence FoMO, while FoMO itself does not significantly influence purchase decisions (β = 0.082, p = 0.167) and does not mediate any of the examined relationships. Conclusion: This study extends the Stimulus–Organism–Response (SOR) framework within digital marketing contexts by demonstrating that FoMO does not significantly mediate purchase decisions in the skincare category. Practical implications are provided for skincare companies seeking to strengthen brand credibility and leverage consumer reviews as quality validation instruments on TikTok.